Analisis peran segmentasi pasar dan strategi diferensiasi produk dalam meningkatkan daya saing perbankan syariah - Indriaputri, Rahmaniyah (Maliki Interdisciplinary Journal, 2025)
This study analyzes the role of product differentiation and market segmentation strategies in improving the competitiveness of Islamic banking, especially in Indonesia. Despite the rapid growth of Islamic banking globally, its market penetration in Indonesia is still low, at around 7%. This research emphasizes the importance of effective marketing strategies, including market segmentation based on demographic, geographic, and psychographic factors, to better meet customer needs and preferences. Product differentiation is also considered crucial for Islamic banks to differentiate themselves from conventional banks and attract customers by offering unique products that comply with Sharia principles. The research method used is qualitative through literature review to evaluate the effectiveness of these strategies in increasing customer satisfaction and loyalty, which in turn contributes to the bank's competitive advantage in a challenging market environment.